2021
DOI: 10.3390/s21062013
|View full text |Cite
|
Sign up to set email alerts
|

Do Radiographic Assessments of Periodontal Bone Loss Improve with Deep Learning Methods for Enhanced Image Resolution?

Abstract: Resolution plays an essential role in oral imaging for periodontal disease assessment. Nevertheless, due to limitations in acquisition tools, a considerable number of oral examinations have low resolution, making the evaluation of this kind of lesion difficult. Recently, the use of deep-learning methods for image resolution improvement has seen an increase in the literature. In this work, we performed two studies to evaluate the effects of using different resolution improvement methods (nearest, bilinear, bicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…In dental surgery, neural networks may be helpful in orthognathic surgery planning, prediction of post-extraction complications, bone lesion detection, and differentiation and implantological treatment planning [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Furthermore, artificial intelligence is spreading into periodontology and in the above-mentioned studies, it was used to evaluate the periodontal bone loss, peri-implant bone loss, and to predict the development of periodontitis due to the psychological features [ 49 , 50 , 51 , 52 , 53 , 54 ]. This review shows that artificial intelligence has developed very fast in recent years and it may become an ordinary tool in modern dentistry in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…In dental surgery, neural networks may be helpful in orthognathic surgery planning, prediction of post-extraction complications, bone lesion detection, and differentiation and implantological treatment planning [ 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Furthermore, artificial intelligence is spreading into periodontology and in the above-mentioned studies, it was used to evaluate the periodontal bone loss, peri-implant bone loss, and to predict the development of periodontitis due to the psychological features [ 49 , 50 , 51 , 52 , 53 , 54 ]. This review shows that artificial intelligence has developed very fast in recent years and it may become an ordinary tool in modern dentistry in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings require some more detailed discussion. First, the most often occurring task for deep learning in the included studies was detecting periodontal and peri‐implant bone loss as diagnostic support on dental images, mainly radiographs 18,19,26,34,35,36,37,38,39 . Very few studies considered other imagery; triangulation of image data and clinical findings were not performed.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Recently, emerging studies showed that AI can be used in orthopaedics. [31][32][33] For example, Yeh et al 30 showed that an AI-baed automatic alignment measure system can locate spinal anatomic landmarks with a high accuracy and produce radiographic parameters that correlated well with operator-based measurements. Yabu et al 34 also demonstrated that convolutional neural network could detect new osteoporotic vertebral fractures utilising magnetic resonance images with performance comparable to that of spine surgeons.…”
Section: Discussionmentioning
confidence: 99%